2010
DOI: 10.1111/j.1600-6143.2010.03266.x
|View full text |Cite
|
Sign up to set email alerts
|

De novoTherapy with Everolimus, Low‐Dose Ciclosporine A, Basiliximab and Steroid Elimination in Pediatric Kidney Transplantation

Abstract: The number of acute rejections and infections after pediatric kidney transplantation (KTX) could not be reduced in the last years. To reduce these events, we investigated a new immunosuppressive protocol in a prospective trial. After KTX, 20 children (median age 12 years, range 1-17) were initially treated with Basiliximab, ciclosporine A (CsA) (trough-level = C0 200-250 ng/mL) and prednisolone. After 2 weeks, CsA dose was reduced to 50% (C0 75-100 ng/mL, after 6 months: 50-75 ng/mL) and everolimus (1.6 mg/m 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 27 publications
7
53
1
Order By: Relevance
“…However, this is in opposition to results from another randomized trial in which wound healing problems were not observed when everolimus was introduced 5-week post-KTX (22). Other side effects observed in this study were generally limited to aphthae, which seldom required treatment (6). In contrast to previous studies that did not include treatment with mTOR inhibitors, the levels of proteinuria and hyperlipidemia were not increased after everolimus treatment.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…However, this is in opposition to results from another randomized trial in which wound healing problems were not observed when everolimus was introduced 5-week post-KTX (22). Other side effects observed in this study were generally limited to aphthae, which seldom required treatment (6). In contrast to previous studies that did not include treatment with mTOR inhibitors, the levels of proteinuria and hyperlipidemia were not increased after everolimus treatment.…”
Section: Discussioncontrasting
confidence: 85%
“…As administered in this study, everolimus did seem to inhibit wound healing after post-KTX surgery (6). However, this is in opposition to results from another randomized trial in which wound healing problems were not observed when everolimus was introduced 5-week post-KTX (22).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Use of everolimus for up to 11 years in pediatric transplant patients has also not been associated with any growth disturbances or impact on sexual maturation. 73,74 Metabolic disturbances Lipid abnormalities (including hypercholesterolemia, hyperlipidemia, and hypertriglyceridemia) may be common with everolimus treatment. 47,71 In TSC patients treated with sirolimus and everolimus, dyslipidemia occurred in 11%-50% of patients.…”
Section: Immunosuppressionmentioning
confidence: 99%
“…32 At 2 weeks after transplant, cyclosporine doses were reduced by 50% (to trough levels of 75-100 ng/mL) and to 50 to 75 ng/mL after 6 months, with everolimus started at 1.6 mg/m²/day and targeted trough levels of 3 to 6 ng/mL. At 6 months after kidney transplant, prednisone was given on alternate days and then stopped 3 months later.…”
Section: Cytomegalovirus Events and Everolimus In Pediatric Patientsmentioning
confidence: 99%